DISCOVERY OF IMPACT DIAMONDS IN A FENNOSCANDIAN CRATER AND EVIDENCE FOR THEIR GENESIS BY SOLID-STATE TRANSFORMATION - Langenhorst F.; Shafranovsky G.I.; Masaitis V.L.; Koivisto M. (My University, 1999)
We report here the first discovery of impact diamonds on the Fennoscandian shield, in the deeply eroded Lappajarvi impact structure, Finland. The tabular morphology and microstructural twin bands provide evidence for the solid-state transformation of graphite to form these diamonds within <1 s. Strong corrosion and coating of surfaces with amorphous carbon may result from the thermal interaction of the diamonds with enclosing impact melt. Because of their unique characteristics, impact diamonds can be easily distinguished from kimberlitic diamonds. In general, durable impact diamonds may thus serve as indicators of ancient impact horizons that could mark biological and climatic catastrophes in Earth's history.